2011
DOI: 10.3233/fi-2011-571
|View full text |Cite
|
Sign up to set email alerts
|

Spiking Neural dP Systems

Abstract: We bring together two topics recently introduced in membrane computing, the much investigated spiking neural P systems (in short, SN P systems), inspired from the way the neurons communicate through spikes, and the dP systems (distributed P systems, with components which "read" strings from the environment and then cooperate in accepting their concatenation). The goal is to introduce SN dP systems, and to this aim we first introduce SN P systems with the possibility to input, at their request, spikes from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
301
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(304 citation statements)
references
References 9 publications
2
301
0
1
Order By: Relevance
“…Spiking neural P systems (SN P systems) [5] are quite a new computational model that are a synergy inspired by P systems and spiking neural networks. It has been shown that these systems are computationally universal [5].…”
Section: Introductionmentioning
confidence: 99%
“…Spiking neural P systems (SN P systems) [5] are quite a new computational model that are a synergy inspired by P systems and spiking neural networks. It has been shown that these systems are computationally universal [5].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, one can find some papers published in the area of membrane computing (or spiking neural P-systems) where a string is encoded in some manner as a natural number and a language is specified as a set of natural numbers (e.g., [3]). Further, recent developments concerning P-automata and its variant called dP-automata are noteworthy in the sense that they may give rise to a new type of computing devices that could be a bridge between P-system theory and the theory of reaction systems and automata ( [5,14,20]).…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics, among others, are meant to capture the workings of a special type of cell known as the neuron. Neurons, such as those in the human brain, communicate or 'compute' by sending indistinct signals more commonly known as action potential or spikes [3]. Inf ormation is then communicated and encoded not by the spikes themselves, since the spikes are unrecognizable from one another, but by (a) the time elapsed between spikes, as well as (b) the number of spikes sent/received from one neuron to another, oftentimes under a certain time interval [3].…”
Section: Parallel Computing: Via Membranesmentioning
confidence: 99%
“…those that spike or transmit signals the moment they are able to do so [4,5]. Variants which allow for delays before a neuron produces a spike, are also available [3]. An SNP system without delay is of the form:…”
Section: Computing With Sn P Systemsmentioning
confidence: 99%